Polymer-Based Nanosystems—A Versatile Delivery Approach - Adelina-Gabriela Niculescu (MDPI AG, 2021)
Polymer-based nanoparticles of tailored size, morphology, and surface properties have attracted increasing attention as carriers for drugs, biomolecules, and genes. By protecting the payload from degradation and maintaining sustained and controlled release of the drug, polymeric nanoparticles can reduce drug clearance, increase their cargo’s stability and solubility, prolong its half-life, and ensure optimal concentration at the target site. The inherent immunomodulatory properties of specific polymer nanoparticles, coupled with their drug encapsulation ability, have raised particular interest in vaccine delivery. This paper aims to review current and emerging drug delivery applications of both branched and linear, natural, and synthetic polymer nanostructures, focusing on their role in vaccine development.